Histomoniasis in Peacock (Pavo cristatus) in the Potiguar Semiarid - Sousa, Ana Caroline Freitas Caetano de; Oliveira, Gabriela Rebouças de; Araújo Júnior, Hélio Noberto de; Prazeres Júnior, Fabiano Rocha; Santos, Caio Sérgio; Feijó, Francisco Marlon Carneiro; Freitas, Carlos Iberê Alves; Braga, Juliana Fortes Vilarinho (Acta Scientiae Veterinariae, 2021)
Background: Histomoniasis is a disease caused by Histomonas meleagridis, a flagellated protozoan that can cause severe necrotizing hepatitis and typhlitis in several bird species. The disease has a cosmopolitan distribution. In experimental infection, peacocks (Pavo spp.) showed susceptibility to histomoniasis, however there are few reports on natural histomoniasis in this species. In northeastern Brazil, reports about its occurrence in avian species are scarce and nonexistent in peacocks. Therefore, this report aims to describe the epidemiological and clinicopathological aspects of a histomoniasis case in a peacock (Pavo cristatus) in the Brazilian semiarid region. Case: A 3-month-old male peacock with a history of apathy and anorexia was attended in the Veterinary Hospital of the Universidade Federal Rural do Semi-Árido (UFERSA), Mossoró, RN, Brazil. The animal was raised extensively in a farm without basic sanitary measures, also with a history of living with animals of different species. After clinical examination, in which intense apathy and weight loss were confirmed, the bird was submitted to emergency therapeutic measures, however there was no clinical improvement and the bird died. At necropsy, intense diffuse bilateral necrotizing typhlitis and multifocal to coalescent necrotizing hepatitis were observed. Fragments of the organs were collected in 10% formaldehyde buffered with phosphate-saline buffer for histopathological analysis and cecal content were collected for microbiological analysis. Histopathology of the cecum revealed transmural necrotizing typhlitis associated with myriads of trophozoites morphologically compatible with Histomonas meleagridis. The same microorganisms observed in association with necrotizing hepatitis lesions, which allowed the diagnosis of histomoniasis. Also, the bacterium Pantoea agglomerans was isolated from the cecal content. Discussion: The macroscopic and microscopic findings allowed the diagnosis and the first recording of histomoniasis in peacock in the semi-arid region of Rio Grande do Norte. The bird was raised in an extensive breeding and without sanitary management, such as the use of anthelmintics, which may favor infection by the nematode Heterakis gallinarum, that’ transmits the protozoan Histomonas meleagridis. The contamination, which begins by the orofecal route, happens through the ingestion of eggs of the nematode contaminated with H. meleagridis that pass through the gastrointestinal tract, reaching the ceca and causing intense lesions in the organ, such as the bilateral transmural typhlitis that we observed in this case. From ceca, the protozoan has access to the bloodstream and reaches the liver, where it causes necrotic hepatitis, also present in the peacock. Both cecal and hepatic lesions were associated with myriads of microorganisms morphologically compatible with H. meleagridis, which allowed the diagnosis of the disease. The challenge in diagnosing this disease occurs mainly due to nonspecific clinical signs, such as apathy and weight loss, the only signs reported by the breeder and observed in this peacock. Confirmation of the occurrence of histomoniasis in any region is important to establish the disease among the differential diagnoses for the species, as in this case. Since this is the first report of peacock histomoniasis in the semi-arid region of Rio Grande do Norte, it is evident the need to consider the disease among possible diagnoses in cases of nonspecific symptoms and it also demonstrates the need to implement control and prophylaxis measures in peacock breeding aiming to avoid losses of birds and economic losses to the breeders and to promote quality of life to the animals.